Cytologic and Functional Alterations of Nasal Mucosa in Smokers: Temporary or Permanent Damage?. (8th January 2015) - Pagliuca, Giulio; Rosato, Chiara; Martellucci, Salvatore; de Vincentiis, Marco; Greco, Antonio; Fusconi, Massimo; De Virgilio, Armando; Gallipoli, Camilla; Simonelli, Marilia; Gallo, Andrea
Abstract : Objective: Tobacco smoke is a significant risk factor for respiratory diseases. The purpose of this study is to analyze the cytologic and functional features of nasal mucosa in smokers, nonsmokers, and ex‐smokers to evaluate if nasal alterations in smokers are permanent or reversible conditions after smoking cessation. Study Design: Case series with planned data collection. Setting: University medical center. Subjects and Methods: Ninety healthy volunteers recruited from the staff of Alfredo Fiorini Hospital, Sapienza University of Rome, were enrolled in this prospective study from October to November 2013. We divided the cases according to smoking habits (smokers, nonsmokers, ex‐smokers). Each group was composed of 30 subjects. Cytologic features of nasal mucosa and effectiveness of nasal mucociliary clearance were studied, focusing on 4 parameters: (1) nasal mucociliary clearance, assessed by saccharin nasal transit time; (2) ratio between the number of ciliated cells and goblet cells, analyzed by microscopic observation of cytologic specimens of nasal mucosa that had undergone May Grunwald Giemsa staining; (3) evaluation of ciliary motility; and (4) time of ciliary movement of ciliated cells analyzed by phase‐contrast microscopy. Results: All parameters were significantly reduced in the smokers compared to the nonsmokers. There were no statistically significant differences between the nonsmoker and ex‐smoker groups. Conclusion: Cigarette smoking causes cytologic modifications of nasal mucosa that influence the effectiveness of mucociliary clearance. Our preliminary study suggests that these changes are not permanent and that nasal mucosa of ex‐smokers recovers normal cytologic and functional features.